Steam Turbine—Quo Vadis? - Gülen, Seyfettin Can (Frontiers in Energy Research, 2021)
In this article, a close look is taken at the state-of-the-art in steam turbine and steam (Rankine) cycle technology within the framework of conventional steam and gas turbine combined cycle power plants, specifically, the bottoming steam (Rankine) cycle of the latter. Using the second law of thermodynamics and the concept of exergy as a guide, cycle and technology factors are calculated to provide a simple but precise (and unassailable) yardstick to assess where the technology was, where it is at present, and how much farther it can go. In addition, the study takes a critical look at an emerging technology, supercritical CO2 cycle, that is being touted as a serious contender for steam turbine’s place in the fossil fuel-fired electric power generation portfolio—as a standalone system or as a waste heat recovery capacity (i.e., combined cycle).